Unhealthy Dieting During the COVID-19 Pandemic: An Opinion Regarding the Harmful Effects on Brain Health - Rentería, Iván; García-Suárez, Patricia Concepción; Moncada-Jiménez, José; Machado-Parra, Juan Pablo; Antunes, Barbara Moura; Lira, Fabio Santos; Jiménez-Maldonado, Alberto (Frontiers in Nutrition, 2022)
Since 2020, the world has been suffering from a pandemic that has affected thousands of people regardless of socio-economic conditions, forcing population to adopt different strategies to prevent and control the advance of disease, one of which is social isolation. Although social isolation is a safe strategy to reduce the spread of the COVID-19, the lockdown increased alarmingly sedentary behavior, excessive gain of adipose tissue depots, which leads to metabolic and inflammatory disruption related with chronic diseases, and especially mental health problems (such as anxiety, depression, sleep disorders, and others), given that the population adopted unhealthy diet patterns increasing consumption of ultra-processed foods, rich in fats and sugars, while reducing fresh and healthy foods. In this mini-review we will discuss how an unhealthy diet can affect brain function and, consequently, be a risk factor for mental health.